Effects of apixaban compared with warfarin as gain in event-free time – a novel assessment of the results of the ARISTOTLE trial. (1st August 2020) - Berglund, Erik; Wallentin, Lars; Oldgren, Jonas; Renlund, Henrik; Alexander, John H; Granger, Christopher B; Hohnloser, Stefan H; Hylek, Elaine M; Lopes, Renato D; McMurray, John JV; Lytsy, Per
Abstract : Background: A novel approach to determine the effect of a treatment is to calculate the delay of event, which estimates the gain of event-free time. The aim of this study was to estimate gains in event-free time for stroke or systemic embolism, death, bleeding events, and the composite of these events, in patients with atrial fibrillation randomized to either warfarin or apixaban in the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation trial (ARISTOTLE). Design: The ARISTOTLE study was a randomized double-blind trial comparing apixaban with warfarin. Methods: Laplace regression was used to estimate the delay in time to the outcomes between the apixaban and the warfarin group in 6, 12, 18 and 22 months of follow-up. Results: The gain in event-free time for apixaban versus warfarin was 181 (95% confidence interval 76 to 287) days for stroke or systemic embolism and 55 (–4 to 114) days for death after 22 months of follow-up. The corresponding gains in event-free times for major and intracranial bleeding were 206 (130 to 281) and 392 (249 to 535) days, respectively. The overall gain for the composite of all these events was a gain of 116 (60 to 171) days. Conclusions: In patients with atrial fibrillation, 22 months of treatment with apixaban, as compared with warfarin, provided gains of approximately 6 months in event-free time for stroke or systemic embolism, 7 months for major bleeding and 13 months for intracranial bleeding.